Justiça de transição, direitos humanos e memória na gestão brasileira da pandemia da COVID-19 - Costa, Débora Dayse Tavares da (My University, 2025)
This study, grounded in research with an emphasis on Contemporary History, focuses on analyzing the institutional stance of the Brazilian state in managing the COVID-19 pandemic from February 2020 to December 2022. The objective is to investigate whether the state's modus operandi constitutes a new case of Transitional Justice in Brazil, prompting the pursuit of the right to truth, memory, and justice, similar to what occurred during the Brazilian civil-military dictatorship, a period marked by numerous violations of fundamental human rights perpetrated by the National State. The study adopts a methodological approach based on bibliographic research, encompassing Brazil?s historical context before and during the COVID-19 pandemic, as well as an analysis of the topic through academic works in the fields of law, historiography, and public health. Additionally, documentary research is conducted using digital media sources, including websites of governmental, legislative, and judicial bodies. The research follows an interdisciplinary methodological framework, aiming to foster dialogue between the fields of Historical Science (and its teaching) and Law, as the subject matter navigates both domains of knowledge. In this regard, the study examines the significant issue of the COVID-19 pandemic from the perspective of its historiographical implications, its developments, and its connection with Transitional Justice. The objective is to provide the necessary tools to ensure the protection and effectiveness of fundamental human rights while preserving the memory of the pandemic in Brazil. As results, multiple indications of governmental violations of such rights (including the right to information, life, and health) were identified. These violations led to recommendations for the indictment of state officials for criminal offenses, the prosecution of those responsible for state management, and the conviction of Brazil in an International Tribunal for crimes against humanity. Finally, as the study?s final product, it is proposed that a cordel (a traditional form of Brazilian popular poetry) based on this research be used as an educational tool in high school classrooms. This aims to encourage students to reflect on the critical period of the pandemic in Brazil and its repercussions, fostering historical awareness of the subject and underscoring the importance of preserving its memory. [resumo fornecido pelo autor]
O presente trabalho, fruto de um estudo com ênfase na História do Tempo Presente, tem como objeto de pesquisa a análise da postura institucional do Estado brasileiro na gestão da pandemia da Covid-19, no período de fevereiro/2020 a dezembro/2022, com vistas a investigar se o modus operandi estatal caracteriza-se como um novo caso de Justiça de Transição no Brasil (ensejando a busca pelo direito à verdade, à memória e à justiça), à semelhança do que ocorrera durante a ditadura civil-militar brasileira, em que se verificou inúmeras violações a direitos humanos fundamentais dos cidadãos, praticadas pelo Estado Nacional. O estudo adota como metodologia a realização de pesquisa bibliográfica abrangendo o contexto histórico do Brasil no período anterior e durante a pandemia da Covid-19, bem como a análise do tema a partir de trabalhos acadêmicos de natureza jurídica, historiográfica e de saúde pública; e ainda pesquisa documental em mídias digitais (sites de órgãos governamentais, legislativos e judiciais). Destaca-se o caráter metodológico interdisciplinar, objetivando o diálogo entre os campos da ciência Histórica (e seu ensino) e do Direito, pois o tema transita por essas áreas do saber. Nessa esteira, o estudo analisa o relevante tema da pandemia da Covid-19 sob a perspectiva de suas implicações historiográficas, seus desdobramentos e vinculação com a Justiça Transicional, com vistas a instrumentalizar a tutela e efetividade dos direitos humanos fundamentais e preservar a memória da pandemia no Brasil. Como resultados, identificam-se indícios de múltiplas violações governamentais a tais direitos (à informação, à vida e à saúde, por exemplo), que culminaram na sugestão do indiciamento pela prática de ilícitos penais e punição dos responsáveis pela gestão estatal, além da condenação em Tribunal Internacional pela prática de crime contra a humanidade. Finalmente, como produto final da pesquisa, sugere-se a utilização de um cordel construído a partir desse estudo, como ferramenta para realização de atividades de sala de aula do Ensino Médio, com vistas a promover nos alunos a reflexão sobre o período crítico da pandemia no Brasil e seus desdobramentos, bem como suscitar a construção da consciência histórica sobre o tema e a importância da preservação de sua memória. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; COVID-19 - História; Direitos humanos - História; Justiça de transição; Memória; History - Study and teaching; COVID-19 - History; Human rights - History; Transitional justice; Memory